PREDICTS: Projecting Responses of Ecological Diversity in Changing Terrestrial Systems - Georgina Mace; Jorn P. W. Scharlemann; Drew W. Purves; Lawrence Hudson; Tim Newbold; Andy Purvis (Frontiers of Biogeography)
The PREDICTS project (www.predicts.org.uk) is a three-year NERC-funded project to model and predict at a global scale how local terrestrial diversity responds to human pressures such as land use, land cover, pollution, invasive species and infrastructure. PREDICTS is a collaboration between Imperial College London, the UNEP World Conservation Monitoring Centre, Microsoft Research Cambridge, UCL and the University of Sussex. In order to meet its aims, the project relies on extensive data describing the diversity and composition of biological communities at a local scale. Such data are collected on a vast scale through the committed efforts of field ecologists. If you have appropriate data that you would be willing to share with us, please get in touch (enquiries@predicts.org.uk). All contributions will be acknowledged appropriately and all data contributors will be included as co-authors on an open-access paper describing the database.